2009
DOI: 10.1542/peds.2008-1634
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Low Risk of Preterm Birth Among Arab Americans in the United States: An Analysis of 617451 Births

Abstract: Maternal birthplace, marital status, and tobacco use may contribute to the preterm birth risk difference between Arab ethnicity and non-Arab white mothers. Additional work is needed to consider the mechanisms relating factors such as maternal birthplace and marital status to ethnic differences in preterm birth risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Among native-born AE mothers, lack of prenatal care and pregnancy-related hypertension were correlates of PTB. El-Sayed et al [6] showed that differences in maternal birthplace and marital status explained the relationship between AE and lower risk for PTB relative to white mothers. Another study found that AE mothers in high AE community contexts were protected against low birth weight (LBW) relative to AE mothers in low AE community contexts [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among native-born AE mothers, lack of prenatal care and pregnancy-related hypertension were correlates of PTB. El-Sayed et al [6] showed that differences in maternal birthplace and marital status explained the relationship between AE and lower risk for PTB relative to white mothers. Another study found that AE mothers in high AE community contexts were protected against low birth weight (LBW) relative to AE mothers in low AE community contexts [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Québec, where 96% of Haitians in Canada are found [4], there has been an effort to document cardiovascular and infectious disease risk factors [29,30]. A larger body of evidence has documented perinatal health inequalities for US ethnic groups especially Blacks and Hispanics [31][32][33][34][35], but also for other minorities including Arabs and native populations [36,37]. Findings tend to vary across ethnic groups, with US Blacks having the poorest outcomes [32] and Arabs relatively favourable outcomes relative to non-Hispanic Whites [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated lower risk for adverse birth outcomes among foreign-born relative to native-born mothers among several ethnic and racial groups, including Blacks [11,22], Hispanics [23][24][25][26], Asian subgroups [11,26], and Arab-Americans [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The predictors of adverse birth outcomes may differ between native and foreign-born mothers in the US [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%